Fiber-based device for refractive index sensing - Wei, Wenting. (2009)
This report documents Final Year Project No. A4021-081, Fiber-based Device for Refractive Index Sensing. An fiber-optic sensor is a fiber based sensor that uses the light transmission property of an optical fiber to detect the changes in the environment, e.g., temperature, strain, or concentration of liquid. Fiber-optic sensors are better than traditional electromagnetic sensor when the sensing location is remote, when there is a sensor size requirement, or when extreme sensitivity is required. In this report, we explored the refractive index (RI) sensing ability based on fiber devices. To be more specific, our main work was to explore the possibility of using optical methods based on fiber devices to achieve a high performance and simple refractive index sensing. We have been mainly worked on three kinds of fiber-optic sensors: side-polished fibers, grating structure with etching, and Mach-Zehnder interferometer. The sensing effect is tested and compared with the refractive index change under the conditions of different NaCl concentrations. The best sensing result is obtained from the interferometric fiber sensor. There was about 1nm wavelength shift achieved for 0.0412 changes in refractive index, corresponding to a RI resolution of 8.26×10-4 -RI unit based on the wavelength resolution, 0.02 nm, of the optical spectrum analyzer. Besides the high sensitivity, the proposed interferometric RI sensor has many other advantages over previously-reported RI sensors. Its advantages include the good compatibility to optical fibers and the low fabrication cost. Most importantly, it has a larger interference cavity over short distance which results in a more stable and significant interference pattern and a much larger extinction ratio of over 10dB. This highly sensitive and yet simple interferometer fiber sensor has many application. For example, it can be used to monitor the concentration of material that is buried in the sea and it will have some applications in the multi-point sensing with its multiplexing ability.